Tapias and mud walls in cuyo and chile (XVI-XIX Centuries - Lacoste, Pablo; Universidad Santiago de Chile (Instituto Carlos Arbeláez Camacho para el patrimonio arquitectónico y urbano, 2014)
This paper studies the walls of mud in the cities of Chile and Cuyo (now Argentina) since the Spanish conquest untilthe late nineteenth century. From archives of original documents, a corpus of documents was built with veritable informationabout 400 walls of mud. The sources deliver data about the parts of these walls (foundations, mud walls,fences), including measures (length, height, thickness), building materials and molds (mud walls, gates, tampers).The relevance of mud walls as patio and home closures was detected. The link between mud walls and the developmentof small holdings, working culture and intensive agriculture in the region (vineyards and orchards) also standsout. The mud walls helped build the foundation for these activities in the region that currently represents one of themain centers of the world’s fruit growing and viticulture.